Pengaruh Pajak, Kepemilikan Asing, Bonus Plan dan Debt Covenant Terhadap Keputusan Perusahaan Untuk Melakukan Transfer Pricing (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2015) - Anita Wahyu Indrasti (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2016)
Transfer pricing phenomenon could be happened based on management motivation in order to tax avoidance or another opportunistic behavior, especially to do wealth transfer among related parties. Ownership stucture can affect management to transfer wealth the themselves or to majority stakeholder. Bonus plan and debt covenant also used by the company to get high profit. This study aimed to examine the effect of tax, ownership of foreign, bonus plan and debt covenant on the company’s decision to perform transfer pricing of all manufacturing company listed in Indonesia Stock Exchange. Sample selection was using purposive sampling method with final sample 26 companies in 104 observation from 2012-2015. The analysis technique used on this study is a binary logistic regression. The result shows that tax and ownership of foreign have significantly effect on the company’s decision to perform transfer pricing. The determination coefficient is 0,379 that means 37.9% transfer pricing is affected by independent variables. While the rest is explained by other variable in outside of this study that can explain transfer pricing